Analysis of the femoral neck from rats in the periestropause treated with oxytocin and submitted to strength training - Fernandes-Breitenbach, Fernanda [UNESP]; Peres-Ueno, Melise Jacon [UNESP]; Santos, Luís Fernando Gadioli [UNESP]; Brito, Victor Gustavo Balera [UNESP]; Castoldi, Robson Chacon [UNESP]; Louzada, Mário Jeferson Quirino [UNESP]; Chaves-Neto, Antonio Hernandes [UNESP]; Oliveira, Sandra Helena Penha de [UNESP]; Dornelles, Rita Cássia Menegati [UNESP] (Elsevier, 2022)
Among the interventions used to prevent osteoporosis in female organisms, strength training (ST) and oxytocin (OT) stand out, as a promising hormone with anabolic action on bone. This study aimed to verify whether the combined action of OT and ST, compared to isolated interventions, potentiates the bone remodeling process of the femoral neck of Wistar rats during periestropause. Forty Wistar rats (18 months) with irregular estrous cycle were randomly distributed into groups: 1-Vehicle (Veh; NaCl 0.15 mol/L ip); 2-Oxytocin (Ot; 134 μg/kg/ip); 3-Strength training (St); 4-Ot + St. The animals of the 1, 2 and 4 groups received two intraperitoneal injections with an interval of 12 h every 30 days, totaling 8 injections at the end of the experimental period (18 to 21 months). The animals in the St and Ot + St groups performed ST on a ladder 3 times a week, maximal voluntary carrying capacity (MVCC) test monthly. After 120 days, the animals were euthanized; the femur was collected for analysis of biomechanical testing, densitometry, bone microtomography, Raman spectroscopy, tissue PCR, and blood for analysis of bone biomarkers, liver damage, and oxidative stress. The main effects in the Ot group were observed in the maximum load and energy in the compression testing (femoral head), and stiffness and energy in the three-points bending testing (femur diaphysis). In addition, the main effects occurred on the bone mineral density (BMD), cortical thickness (Ct.Th), number of pores (Po.N), polar moment of inertia (J), trabecular thickness (Tb.Th), and connectivity density (Conn.Dn), Bone alkaline phosphatase (Alp), Tumor necrosis factor receptor superfamily member 11b (Opg), Tumor necrosis factor ligand superfamily member 11 (Rankl) and Cathepsin K (Ctsk) expression. There was an effect in the tartrate-resistant acid phosphatase (TRAP) and alkaline phosphatase (ALP). In the St group, the main effect was observed on the energy (compression and the three-points bending), stiffness, aBMD, BMD, cortical bone area (Ct.Ar), Po.N, trabecular bone volume (BV/TV), Tb.Th and in the mineralization ratio (ѵ1PO4/proline), Runt-related transcription factor 2 (Runx2), Bone morphogenetic protein 2 (Bmp2), Alp, Osteopontin/secreted phosphoprotein 1 (Opn/Spp1), Opg, Tumor necrosis factor receptor superfamily member 11ª (Rank), Rankl, Ctsk expression. There was an effect in the TRAP and ALP. The interaction in the combination of therapies in the Ot + St group was verified in energy to maximum load (compression and three-points bending testing), stiffness, BMD, Ct.Th, J, Tb.Th and ѵ1PO4/proline. In the gene analysis there was interaction in the Runx2, Osterix/Sp7 transcription factor (Osx/Sp7), Bmp2, Alp, Osteocalcin/Bone gamma-carboxyglutamate protein (Ocn/Bglap), Opg, Rankl and Acid phosphatase 5, tartrate resistant (Trap/Acp5) expression. In addition, the combination of OT and ST resulted in a higher maximum load compared to the Veh group, with higher BV/TV than the Ot group, higher Rankl and Ctsk expression than Veh and Ot groups, and lower Po.N and lower activity of TRAP than the other groups. In oxidative stress, total antioxidant capacity (TAC) was lower. These results showed that the combination of interventions is a promising anabolic strategy for the prevention of osteoporosis in the period of periestropause, standing out from the effects of isolated interventions.
Keywords: Aging; Femur neck; Osteoporosis; Oxytocin; Strength training